Is there a Correlation Between Degree of Radiologic Lumbar Spinal Stenosis and its Clinical Manifestation?. Issue 8 (October 2018) - Andrasinova, Tereza; Adamova, Blanka; Buskova, Jana; Kerkovsky, Milos; Jarkovsky, Jiri; Bednarik, Josef
Abstract : Study Design: This was an observational cross-sectional study. Objective: The purpose of this study was to evaluate whether the degree of stenosis on magnetic resonance imaging (MRI) relates to the severity of clinical symptoms, disability, or neurological deficit in patients with symptomatic central lumbar spinal stenosis (LSS). Summary of Background Data: The relationship between radiologic findings and the clinical manifestations of LSS remains unclear. Materials and Methods: A total of 84 patients (42 men, median age 70 y) with neurogenic claudication and central degenerative LSS were included in the study. The MRI parameters describing severity (anteroposterior diameter of dural sac, cross-sectional area of the dural sac, stenosis ratio, and Schizas qualitative morphologic classification were evaluated at maximum stenotic level) and the extent of stenosis (the number of central stenotic levels) were correlated to symptoms (pain intensity, walking capacity), functional disability (measured in terms of the Oswestry Disability Index), and neurological signs of LSS (neurological status was evaluated and scored by Neurological Impairment Score in LSS). Results: A statistically significant correlation emerged only between the Neurological Impairment Score in LSS and Schizas morphologic classification ( P =0.006). Pain intensity, walking capacity, and functional disability displayed no correlation with the MRI parameters of LSS. Conclusions: LSS is a clinicoradiologic syndrome with complex relationships between degree of radiologic stenosis disclosed by MRI and clinical manifestations. Neurological impairment in the lower extremities reflects the degree of morphologic LSS on MRI. This study did not identify any association between the degree of stenosis and functional disability, pain intensity, or walking capacity. Level of Evidence: Level II.